DISP3 promotes proliferation and delays differentiation of neural progenitor cells - Zíková, Martina; Konířová, Jana; Ditrychová, Karolína; Corlett, Alicia; Kolář, Michal; Bartůněk, Petr (FEBS letters, 2014)
DISP3 (PTCHD2), a sterol-sensing domain-containing protein, is highly expressed in neural tissue but its role in neural differentiation is unknown. In the present study we used a multipotent cerebellar progenitor cell line, C17.2, to investigate the impact of DISP3 on the proliferation and differentiation of neural precursors. We found that ectopically expressed DISP3 promotes cell proliferation and alters expression of genes that are involved in tumorigenesis. Finally, the differentiation profile of DISP3-expressing cells was altered, as evidenced by delayed expression of neural specific markers and a reduced capacity to undergo neural differentiation.
Keywords: Gene Expression Regulation; Cell Line; Cell Proliferation; Brain; membránové proteiny; Cancer; buněčná diferenciace; Membrane Proteins; Proliferation; Neural cells; metabolismus lipidů; lidé; Neural Stem Cells; Humans; regulace genové exprese; Lipid Metabolism; mozek; buněčné linie; proliferace buněk; Differentiation; Lipids; nervové kmenové buňky; Cell Differentiation